2015
DOI: 10.17221/26/2014-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effect of formulated bioorganic containing Burkholderia GanoEB2 in suppressing Ganoderma disease in oil palm seedlings

Abstract: Ili Nadhrah N., Nulit R., Nurrashyeda R., Idris A.S. (2015): Effect of formulated bioorganic containing Burkholderia GanoEB2 in suppressing Ganoderma disease in oil palm seedlings. Plant Protect. Sci., 51: 80-87.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Severity indices in the last assessment of the experiment ranged from 23 to 34%, and was lower than those reported by [ 29 ] and [ 51 ] who used the same disease severity scale in seedlings artificially inoculated with G. boninense , with values of 87 and 90.4%, respectively. However, our severity values are closer to those reported by [ 48 ] for G. zonatum , with values of 34.08 and 43.78% for two isolates analyzed in the study.…”
Section: Discussioncontrasting
confidence: 66%
“…Severity indices in the last assessment of the experiment ranged from 23 to 34%, and was lower than those reported by [ 29 ] and [ 51 ] who used the same disease severity scale in seedlings artificially inoculated with G. boninense , with values of 87 and 90.4%, respectively. However, our severity values are closer to those reported by [ 48 ] for G. zonatum , with values of 34.08 and 43.78% for two isolates analyzed in the study.…”
Section: Discussioncontrasting
confidence: 66%
“…As the important origin of primary infection, residual pathogens on dropped-blossoms and fruits play crucial role in epidemic of litchi downy blight [40]. Our ndings indicated that organic mulching application reduced disease incidence and manipulated the soil microbial community structure, especially the increasing bacterial families such as Burkholderia, Bacillus, and Paenibacillus, which have been proved to possess antagonistic activities and contribute to disease suppressiveness [41][42][43]. Moreover, the frequent occurrence of speci c bene cial fungal species, such as Trichoderma sp.…”
Section: Discussionmentioning
confidence: 90%
“…Bukholderia is known as biofilm producer [21] and also known as antifungal bacteria against Ganoderma boninense, a pathogen of oil palm; [22] whereas Pasteuria is soil nematode endophyte [22]. In contrary, Streptomyces was the most dominant genus in the first cluster (16.5 %; Fig.…”
Section: Ecological Function Analysis Of Dominant Culturable Bacteriamentioning
confidence: 99%